PEMBUATAN VIDEO DOKUMENTASI EVENT ORGANIZER BAGI PERUSAHAAN PT. KALAMATA KOMUNIKA IDEALEEMA DI BANDUNG - Asep Lukman (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Documentation video is a video or photo that captures an important moment in an event. If a client wants to collaborate or needs and event organizer service, the main thing he sees is the portofolio, brand value and social media. In the modern era social media is now commonplace among Indonesia people, this is a great opportunity for a company to promote the services or products it sells.The main problem experienced by companies engaged in event organizer services usually occurs because of inadequate preparation, poor coordination, mistakes when compiling a budget, inexperienced event organizer,  and also the lack of content or visual creative that can provide more assessment for prospective clients or customers, because people tend to look at their social media fist before contacting the event organizer it self. The number of services or competitors in this field, make companies think more creatively how their business can progress, grow and be able to compete with other brands. Therefore, a company, especially one that is engaged in services such as event organizers, requires documentation in the form of photos and videos which can later be used as a company portfolio or become content on social media, company branding and become proof of the continuity of an event.